2006
DOI: 10.1080/08039480600583597
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of future suicide in suicide attempters – A comparison between suicides and matched survivors

Abstract: The objective of this study was to find risk factors for suicide by looking for clinical and care/treatment consumption differences between 15 hospitalized suicide attempters, who later committed suicide ("completers"), and 15 suicide attempters who did not ("non-completers"), matched according to sex, age and principal diagnosis. Completers had significantly more often attempted suicide after the index admission. After index, completers had received more psychiatric care and treatment than non-completers. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
1
19
0
5
Order By: Relevance
“…High levels of suicidal intent in this population may have implications for optimal cut-off scores for suicide prediction in suicide attempters in general, as other research has suggested [47,48]. This finding warrants further examination.…”
Section: Suicidal Intentmentioning
confidence: 70%
“…High levels of suicidal intent in this population may have implications for optimal cut-off scores for suicide prediction in suicide attempters in general, as other research has suggested [47,48]. This finding warrants further examination.…”
Section: Suicidal Intentmentioning
confidence: 70%
“…Excepting a recent study comparing suicide completers with BPD to individuals with BPD in treatment at outpatient psychiatric centers (McGirr, Paris, Lesage et al, 2007), among attempters, across diagnoses, individuals with higher numbers of prior attempts are also at an increased risk for completing suicide (Beck, Schuyler, & Herman, 1974;Goldstein, Black, Nasrallah et al, 1991;Holmstrand, Nimeus, & Traskman-Bendz, 2006;Kullgren, 1988). Increased lifetime attempts have also been found to be more prevalent among highlethality BPD attempters than low-lethality BPD attempters (Soloff, Fabio, Kelly et al, 2005;Soloff, Lis, Kelly et al, 1994) and among young adults who make HLSAs as compared to non-suicidal controls (Beautrais, 2003).…”
Section: Traits: Impulsivity and Aggressionmentioning
confidence: 96%
“…For example, rates of clinically elevated psychoticism in the first 2 years post partum were (30-54%), paranoid ideation (30-53%), depression (18-36%), hostility (24-31%) and anxiety (15-27%). Elevation of these symptom domains have the potential for serious consequences for mothers including suicide (Holmstrand et al 2006), loss of infant custody (Minnes et al 2008) and increased rates of domestic violence (Nixon et al 2004;Stuart et al 2006). High rates of maternal psychopathology pose threats to infant well-being as well.…”
Section: Discussionmentioning
confidence: 99%